Answer:
-4
Step-by-step explanation:
All you have to do is find the change of y over the change of x.
So let R equal to the revenue of the company
x be the number of rides
since the cost per ride is $ 35
so the equation for revenue is
R = 35x
the profit can also be solve
profit = revenue - cost
profit = R - C
profit = 35x - 15x - 2000
profit = 20x - 2000
<h2>
<em>Answer:</em></h2><h2>
<em>x^</em><em>2</em><em>+</em><em>4</em><em> </em><em>and </em><em>X+</em><em>2</em></h2>
<em>Solution,</em>
<em>x^</em><em>4</em><em>-</em><em>1</em><em>6</em>
<em>=</em><em> </em><em>(</em><em>X^</em><em>2</em><em>)</em><em>^</em><em>2</em><em>-</em><em>(</em><em>4</em><em>)</em><em>^</em><em>2</em>
<em>Use </em><em>the </em><em>formula(</em><em>a^</em><em>2</em><em>-</em><em>b</em><em>^</em><em>2</em><em>)</em>
<em>=</em><em> </em><em>(</em><em>x^</em><em>2</em><em>+</em><em>4</em><em>)</em><em>(</em><em>x^</em><em>2</em><em>-</em><em>4</em><em>)</em>
<em>=</em><em>(</em><em>x^</em><em>2</em><em>+</em><em>4</em><em>)</em><em>(</em><em>x^</em><em>2</em><em>-</em><em>2</em><em>^</em><em>2</em><em>)</em>
<em>=</em><em>(</em><em>x^</em><em>2</em><em>+</em><em>4</em><em>)</em><em>(</em><em>X+</em><em>2</em><em>)</em><em>(</em><em>x-2)</em>
<em>Hope </em><em>it</em><em> helps</em>
<em>Good </em><em>luck</em><em> on</em><em> your</em><em> assignment</em>
Answer:
18
Step-by-step explanation:
Factor the numerator and denominator and cancel the common factors.
Hope this helps plz give brainliest.
Answer:
y = 3^(1 + x)
Step-by-step explanation:
Notice that each time x increases by 1, y increases by a factor of 3.
Thus, the required equation has the form y = 3^x.
Check: If x = 0, do we get 3? No. Therefore we must modify the exponent:
y = 3^(1 + x)
Check: If x = 0, do we get 3? 3^(1 + 0) = 3 (correct)
If x = 2, do we get 27? 3(1 + 2) = 3^3 + 27 (correct)